2018
DOI: 10.1186/s12889-018-5663-7
|View full text |Cite
|
Sign up to set email alerts
|

Exploring patterns of response across the lifespan: the Cambridge Centre for Ageing and Neuroscience (Cam-CAN) study

Abstract: BackgroundWith declining rates of participation in epidemiological studies there is an important need to attempt to understand what factors might affect response. This study examines the pattern of response at different adult ages within a contemporary cross-sectional population-based cohort, the Cambridge Centre for Ageing and Neuroscience (Cam-CAN).MethodsUsing logistic regression, we investigated associations between age, gender and Townsend deprivation level for both participants and non-participants. Weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 18 publications
(27 reference statements)
0
28
0
Order By: Relevance
“…T A B L E 1 Participants' demographic information, grouped by decile in accordance with the original design of the Cam-CAN cohort (Green et al, 2018;Shafto et al, 2014 The EPI data were unwarped (using field-map images) to compensate for magnetic field inhomogeneities, realigned to correct for motion, and slice-time corrected to the middle slice. The normalization parameters from the T1 image processing were then applied to warp functional images into MNI space.…”
Section: Fmri Image Acquisition and Processingmentioning
confidence: 99%
“…T A B L E 1 Participants' demographic information, grouped by decile in accordance with the original design of the Cam-CAN cohort (Green et al, 2018;Shafto et al, 2014 The EPI data were unwarped (using field-map images) to compensate for magnetic field inhomogeneities, realigned to correct for motion, and slice-time corrected to the middle slice. The normalization parameters from the T1 image processing were then applied to warp functional images into MNI space.…”
Section: Fmri Image Acquisition and Processingmentioning
confidence: 99%
“…Further information about the recruitment, exclusion criteria, and contents of the testing stages can be found in Shafto et al 2014, Taylor et al (2017), and Green et al (2018). Further details of exclusion and refusals in Stage 1 can be found in Green et al (2018) and in Stages 2 and 3 can be found in Schweizer et al (2019). Further details on the contents of the Cam-CAN data repository and information on how to access it can be found in Taylor et al (2017) or at cam-can.com.…”
Section: Cam-can Project: Recruitment Testing Stages and Data Reposmentioning
confidence: 99%
“…Participants were recruited into Stage 1 from the Cambridge, UK community via their general practitioner (GP) surgeries. Green, Bennett, Brayne, Cam-CAN, and Matthews (2018) provide details about recruitment and exclusion, where out of 7,616 eligible participants who were initially approached, 2,680 (35.2%) were ultimately interviewed. Active refusals such as being too busy (61% of refusals; N = 3,008) and illness (35.6% of refusals; N = 1,756) made up the majority of refusals at this stage.…”
Section: Cam-can Project: Recruitment Testing Stages and Data Repositorymentioning
confidence: 99%
See 2 more Smart Citations